Comparison Of Reading Aloud Strategies Versus Silent Reading Strategies Used On Pakistani University Students’ Reading Comparison For Reading Proficiency & Literal Reading Skills - Sajid, Muhammad Khalid Mehmood; Hafizoah, Kassim (EuroJournals Publishing, Inc., 2019)
Reading is the best way to give knowledge. Reading is an essential part of learning. No one can neglect its importance. There are many strategies for reading. Among them, one is silent reading strategy while another one is reading aloud strategy. Pakistan is a developing country where the English language is used as a second language because the national language is Urdu. Students’ base for English conversation and writing is poor in such condition reading aloud strategy is important especially for poor readers. No one can neglect its importance, and that is why the importance of read-aloud strategy is increasing as compared to silent reading strategy. The present study was conducted at a Pakistani university. A comparative analysis of read-aloud strategies versus silent reading strategies was done. Data was collected from M.Phil. Masters, and BS program students through questionnaires. The study is based on an experimental and questionnaires were used, the targeted sample was from English department in which 20 students and teachers of BS program were selected while 170 respondents including 100 male and 70 female were selected for the questionnaire. Findings show that read aloud strategies are better than silent reading because in Pakistan English language used as a second language. Students had shown a better response for reading aloud strategies for reading proficiency and literal reading skills.